DEOXYNIVALONOL IN PIG FEED: AN OVERVIEW ON OCCURENCE IN THE PERIOD OF FIVE YEARS (2019-2024) - Stojanovska dimzoska, Biljana; Dushica, Koceva; Gordana, Ilievska; Angeleska, Aleksandra; Dimitrieska Stojkovikj, Elizabeta; Uzunov, Risto; Blagoevska, Katerina (Faculty of Veterinary Medicine - Skopje, 2024)
Deoxynivalenol (DON) belongs to the large group of mycotoxins called trichothecenes, occurring predominantly in cereal grains such as wheat, barley, oats, rye and maize. DON is primarily produced by the pathogenic Fusarium fungi which grow on the cereals in the field, preferably at temperate climates as they are commonly found in Europe. Cereal grains intended for food and feed may also become contaminated during storage. Deoxynivalenol can make animals refuse feed even at low doses, and at larger concentrations, it can cause vomiting, leading to growth depression, increase an animal's susceptibility to infections, cause diarrhea, and hemorrhage. DON also has been connected with the human disease ATA (alimentary toxic aleukia). DON is chemically stable and extent resistant to thermal processing. Because it is difficult to neutralize or remove DON from feed, it is important to detect contamination by these trichothecene mycotoxin. At least 40 countries have set maximum levels (MRLs) or guidelines for DON in animal feed on a global scale, ranging from 0.9 to 12 mg/kg. Total of 25 complementary feedingstuffs for fattening pigs, 28 feed samples for sows, 19 samples for piglets, 10 corn and 10 barley samples were analyzed in our laboratory for presence of DON. ELISA screening method was used for determination, which is validated (in compliance with 2002/657/EC) and accredited (ISO 17025). The results were evaluated according to Macedonian legislation (Official Gazette 53/2013) which are in accordance with European regulations (2006/576/EU). All cereal samples (corn and barley) were with DON concentration below LOD (45 µg/kg). Ten (10) out of 28 samples for sows (35.7%) were in concentration range of 65 – 898.74 µg/kg. DON was found in 6 out of 25 samples for fattening pigs (24%) in concentration range of 40.63 – 800 µg/kg. Both of these categories of pig feed fulfill the criteria set in the regulations (5 mg/kg for complementary and complete feedingstuffs). Concerning the feed for piglets, 6 samples out of 19 (31.5%) shown presence of DON in the concentration range of 77.3 – 143 µg/kg. MRL for pigs is set on 0.9 mg/kg. Although all feedingstuffs for pigs do not surpassed MRLs values proposed within the regulation, it is important to acknowledge the existence of DON, and mycotoxins in general, in feed samples. The strategies to be undertaken in the future should be aimed at prevention, elimination and detoxification, as three basic approaches in the fight against mycotoxins and their entry into food chain.
Keywords: deoxynivalenol, pig feed, ELISA